Strategic issues for reducing patient waiting time and improving satisfaction with services at the Out-patient department of the First Affiliated Hospital, Kunming Medical College, people's Republic of China - Pei Likun (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 1993